2009
DOI: 10.3758/brm.41.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Timing accuracy of Web experiments: A case study using the WebExp software package

Abstract: Although internet-based experiments are gaining in popularity, most studies rely on directly evaluating participants' responses, rather than reaction times. Here we present two experiments which demonstrate the feasibility of collecting response latency data over the world-wide web, using WebExp, a software package designed to run psychological experiments over the internet. Experiment 1 uses WebExp to collect measurements for known time intervals (generated using keyboard repetition). The resulting measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 24 publications
1
64
0
Order By: Relevance
“…There have been several successful attempts to replicate effects previously observed offline using online samples: Reimers and Maylor (2005) replicated the effects of age differences on task-switching performance measured with RTs; Keller et al (2009) replicated RT findings from a self-paced reading study; Simcox and Fiez (2014) reproduced flanker and lexical decision effects; and Crump et al (2013) replicated Stroop, task-switching, flanker, Simon, visual-cuing, and masked-priming effects. Although these findings show the usefulness of online studies, they do not allow for a direct comparison between offline and online results, because they were obtained in different studies.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…There have been several successful attempts to replicate effects previously observed offline using online samples: Reimers and Maylor (2005) replicated the effects of age differences on task-switching performance measured with RTs; Keller et al (2009) replicated RT findings from a self-paced reading study; Simcox and Fiez (2014) reproduced flanker and lexical decision effects; and Crump et al (2013) replicated Stroop, task-switching, flanker, Simon, visual-cuing, and masked-priming effects. Although these findings show the usefulness of online studies, they do not allow for a direct comparison between offline and online results, because they were obtained in different studies.…”
mentioning
confidence: 67%
“…Schubert et al used their own Flash-based scripting library, ScriptingRT (Schubert, Murteira, Collins, & Lopes, 2013). ScriptingRT was slightly slower and more deviant than most of the offline software, but in absolute terms the SDs were less than 5 ms. Keller et al used repetitive keypress events generated by the operating system when a key was held down to test their Java-based Webexp software (Keller, Gunasekharan, Mayo, & Corley, 2009). They found that although there was a delay at shorter time intervals, it was not big (about 12 ms on 300 ms of repetitive keypresses), and the SDs were less than 5 ms in most of the conditions.…”
mentioning
confidence: 99%
“…For specific paradigms, however, specialized software packages may be more suitable. For example, the Functional Measurement Experiment Builder Suite (Mairesse et al, 2008), for conducting experiments using the functional measurement paradigm, or WebExp (Keller, Subahshini, Mayo, & Corley, 2009), for conducting simple Web experiments, are both Java-based applications, and therefore are also platform independent, but they require a lot less prior programming knowledge.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…small differences in response time" (Skitka & Sargis, 2006, p. 547). Thus, although several well-established reaction time effects have been replicated in Web-based research (e.g., Crump, McDonnell, & Gureckis, 2013;Keller, Gunasekharan, Mayo, & Corley, 2009;Simcox & Fiez, 2014), skepticism remains widespread-for at least three reasons.…”
mentioning
confidence: 99%